Rancang Bangun E- Commerce Toko Ainun Tas Menggunakan Metode Economic Order Quantity dan Perilaku Konsumen Berbasis Web - Utami, Lola Citra; Suendri, Suendri; Sibarani, Fathiya Hasyifah (Teknik Informatika Fakultas Ilmu Komputer, 2025)
Ainun Bag Store is a fashion retail business specializing in the sale of high-quality women’s bags, both locally made and imported, at affordable prices. However, the store still relies on manual systems for managing operations, marketing, transactions, and inventory. Customers are required to visit the store directly to make purchases, and all transaction records are manually written in physical ledgers. This conventional method has several limitations, such as inefficient inventory management, potential human error, and a lack of accessible sales data. Additionally, consumer behavior—such as satisfaction with service—has a direct impact on sales performance. This study aims to design and develop a web-based e-commerce platform for Ainun Bag Store by applying the Economic Order Quantity (EOQ) method and Consumer Behavior Analysis. The EOQ method is implemented to optimize stock levels and reduce storage costs, while Consumer Behavior Analysis is used to understand customer preferences and improve overall satisfaction.